Cacna1c Hemizygosity Results in Aberrant Fear Conditioning to Neutral Stimuli. (7th January 2020) - Moon, Anna L; Brydges, Nichola M; Wilkinson, Lawrence S; Hall, Jeremy; Thomas, Kerrie L
Abstract: CACNA1C, a gene that encodes an alpha-1 subunit of L-type voltage-gated calcium channels, has been strongly associated with psychiatric disorders including schizophrenia and bipolar disorder. An important objective is to understand how variation in this gene can lead to an increased risk of psychopathology. Altered associative learning has also been implicated in the pathology of psychiatric disorders, particularly in the manifestation of psychotic symptoms. In this study, we utilize auditory-cued fear memory paradigms in order to investigate whether associative learning is altered in rats hemizygous for the Cacna1c gene. Cacna1c hemizygous ( Cacna1c +/− ) rats and their wild-type littermates were exposed to either delay, trace, or unpaired auditory fear conditioning. All rats received a Context Recall (24 h post-conditioning) and a Cue Recall (48 h post-conditioning) to test their fear responses. In the delay condition, which results in strong conditioning to the cue in wild-type animals, Cacna1c +/− rats showed increased fear responses to the context. In the trace condition, which results in strong conditioning to the context in wild-type animals, Cacna1c +/− rats showed increased fear responses to the cue. Finally, in the unpaired condition, Cacna1c +/− rats showed increased fear responses to both context and cue. These results indicate that Cacna1c heterozygous rats show aberrantly enhanced fear responses to inappropriate cues, consistent with key models of psychosis.